Justification of conditions for the creation and mechanism of interaction among participants in a cluster association of enterprises - Pulina, Tetiana; Maliarenko, Yaroslav; Tkachova, Natalia (Management and Entrepreneurship: Trends of Development, 2023)
The article defines the conditions for the creation and justification of a mechanism for interaction among participants in a cluster association of enterprises in the engineering industry. An assessment of the cluster potential of the engineering sector in the Zaporizhzhia region has been conducted based on calculations of localization coefficients, production per capita, and specialization. The assessment results identify the conditions for creating an engineering cluster. The organizational structure for managing a regional engineering cluster is analyzed, along with the influence of external environmental factors on cluster activities. The justified organizational structure for cluster management ensures active horizontal links between participants and coordinates the flow of resources, information, innovations, and other production factors across the cluster’s main sectors: specialization sector, financial and insurance sector, science, development and innovation sector, suppliers sector, specialized services sector, and the cluster coordinator. The study finds that macroeconomic factors, regional infrastructure, external investors, external suppliers, consumers, and government bodies have a significant impact on cluster functioning. A proposed organizational-economic mechanism for cluster interaction establishes and coordinates the flow of resources (material and financial), information, innovations, and other production factors between the main sectors of the cluster, including the specialization sector (subsystem for product value formation), financial and insurance sector, science, development and innovation sector, suppliers sector, specialized services sector, and cluster coordinator. The proposed concept for the development of a regional engineering cluster in the Zaporizhzhia region will allow enterprises to effectively utilize production and innovation potential, increase the share of innovative products, and significantly improve the socio-economic indicators of the Zaporizhzhia region's development.JEL Classification: L6, R1, L2, O3